Cost Analysis of Drug Information Services at the Mental Hospital in Saudi Arabia - Alomi, Yousef Ahmed; Qahtani, Nada Al; Alsulami, Nora; Mashouf Al Qahtani, Mohamed; Almansor, Fahad Abdallah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the cost analysis of drug information services at the mental hospital in Saudi Arabia. Method: It retrospective cost analysis of drug information services past four years and a half at a mental hospital in Riyadh city, Saudi Arabia. It 500-bed of Psychiatry and addition hospitals in Riyadh city. The analysis included the variable expenses included personal cost, material and supply cost, Fixed expenses including direct cost, non-salary cost, and overhead cost The cost drives from Ministry of Health information database. All cost used US dollar currency. Results: The estimated total cost of delivery of the drug information services for four years and a half was (117,362.52) USD and (26,080.56) USD annually. The majority of cost came from personal cost (81.80%, direct cost (5.24%) followed by overhead cost (5.15%) and Non-Salary cost (4.99%). The average cost of answering drug information inquiries (108.27) USD. The highest cost of delivery of inquiries per type was an adverse drug reaction, stability and poisoning and toxicology (3.15). The highest cost delivered drug information center for each inquiry to healthcare providers as follows; the physician cost (4.2) USD, pharmacist cost (3.15) USD, and nurse cost (1.575). The highest cost utilized drug information resources for each inquiry as follows; Prescribing guidelines in psychiatry (340.20) USD, Drug.com (275.10) USD, and Medscape was (236.25) USD. Conclusion: The cost of drug information services was justified despite the limited resources. More drug information services needed to expand cover more services, healthcare providers, and patients.
Keywords: Cost analysis; Drug information; Mental hospital; Ministry of Health; Saudi Arabia